A role played by the All-Union Communist Party (Bolsheviks) Central Committee Bureau for Lithuania in suppressing resistance of partisans (November 1944–March 1947) - Pocius, Mindaugas (Genocidas ir rezistencija, 2017)
The article examines the role of one of the main administrative institutions of the Soviet occupation, the All-Union Communist Party (Bolsheviks) Central Committee Bureau for Lithuanian Affairs, in organising the suppression of the anti-Soviet resistance in 1944– 1947. The research attempts to reveal how the fight against the resistance was managed, what solutions were proposed by the Moscow emissaries, what was their influence in suppressing the resistance, and what was the role of the ACP(B) CC Bureau for Lithuanian Affairs within the overall system of repression.